2017
DOI: 10.1093/ee/nvw169
|View full text |Cite
|
Sign up to set email alerts
|

Do Distinct Biomes Influence the Cuticular Chemical Profile in Orchid Bees?

Abstract: Cuticular chemical profiles of Euglossa cordata L. males were analyzed to test whether ecological predictors affect their composition and relative proportion. Males were collected in areas of Caatinga and Atlantic Forest from Brazil during two distinct seasonal periods. We found 48 compounds from the cuticular extracts of males, which consisted of hydrocarbons (71.39%), acetates (16.79%), esters (10.5%), alcohols and others (1.31%). We verified that when specimens were separated between biomes, they did not sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For example, the fact that pentacosane levels were found to be 9.88% in male Euglossa cordata suggests that this molecule is essential in attracting female insects. 56 Analysis conducted on S. orientalis showed that the most common fatty acids are palmitic, stearic, oleic, linoleic, aliphalinolenic, and stearic acids. Previous studies on orchids have reported varying amounts of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the fact that pentacosane levels were found to be 9.88% in male Euglossa cordata suggests that this molecule is essential in attracting female insects. 56 Analysis conducted on S. orientalis showed that the most common fatty acids are palmitic, stearic, oleic, linoleic, aliphalinolenic, and stearic acids. Previous studies on orchids have reported varying amounts of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, examining the chemical profiles of cuticles in studies provides insights into the role of scent and pheromones in the interactions between male and female insects. For example, the fact that pentacosane levels were found to be 9.88% in male Euglossa cordata suggests that this molecule is essential in attracting female insects …”
Section: Discussionmentioning
confidence: 99%